PENGARUH PENERAPAN GCG, AUDIT INTERNAL DAN WHISTLEBLOWING TERHADAP PENCEGAHAN FRAUD DI LPD DENPASAR SELATAN - Adnyani, Ni Kadek Dwi; Hutnaleontina, Putu Nuniek (Hita Akuntansi dan Keuangan, 2022)
Fraud is a variety of fraudulent acts, whether committed intentionally or unintentionally by third parties. The targets of extortion incorporate forestalling misrepresentation in all lines of the association, hindering expected culprits., making it difficult for fraud perpetrators to move, recognizing high-risk exercises and control shortcomings, and making demands or forcing sanctions on fraud culprits. The motivation behind this study was with determine the impact of implementing good corporate governance, the role of internal audit and the whistleblowing system on the prevention of fraud at Village Credit Institutions in South Denpasar District. The population in this study were all LPD in South Denpasar as many as 10 LPD. The method of determining the sample using the saturated sampling method so that obtained 117 respondents. The type of research used is quantitative. The analytical method used is multiple linear regression. Based on the analysis test results, it is found that good corporate governance had a beneficial outcome on misrepresentation. Meanwhile, the role of internal audit and the whistleblowing system had a positive and insignificant effect on fraud